Horizontal auger boring projects (American Society of Civil Engineers, 2004)
Annotation "This manual covers the horizontal auger boring method, providing the instructions for a safe, productive, and efficient installation of pipelines for road crossing. The manual is divided into five sections; the first section is an introduction that includes history, recent innovations, applicable documents, typical applications, and a glossary of terms. The proceeding sections provide important information on the planning, design, pre-construction phase, and construction phases of the horizontal auger boring methods. The last section includes a list of references. New and experienced engineers, utility contractors, and other professionals working in pipeline construction will find this manual useful by providing introductory and advanced topics for safe, cost-effective, and productive design and construction of horizontal auger boring projects."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Keywords: Pipelines -- Design and construction.; Trenchless construction.; Boring.; elektronické knihy; electronic books